R-Loops as Cellular Regulators and Genomic Threats - Crossley, Madzia P; Bocek, Michael; Cimprich, Karlene A (Molecular cell, 2019)
During transcription, the nascent RNA strand can base pair with its template DNA, displacing the non-template strand as ssDNA and forming a structure called an R-loop. R-loops are common across many domains of life and cause DNA damage in certain contexts. In this review, we summarize recent results implicating R-loops as important regulators of cellular processes such as transcription termination, gene regulation, and DNA repair. We also highlight recent work suggesting that R-loops can be problematic to cells as blocks to efficient transcription and replication that trigger the DNA damage response. Finally, we discuss how R-loops may contribute to cancer, neurodegeneration, and inflammatory diseases and compare the available next-generation sequencing-based approaches to map R-loops genome wide.